Periodontitis as a risk factor of atherosclerosis - Bartova, Jirina; Sommerova, Pavla; Lyuya-Mi, Yelena; Mysak, Jaroslav; Prochazkova, Jarmila; Duskova, Jana; Janatova, Tatjana; Podzimek, Stepan (Journal of immunology research, 2014)
Over the last two decades, the amount of evidence corroborating an association between dental plaque bacteria and coronary diseases that develop as a result of atherosclerosis has increased. These findings have brought a new aspect to the etiology of the disease. There are several mechanisms by which dental plaque bacteria may initiate or worsen atherosclerotic processes: activation of innate immunity, bacteremia related to dental treatment, and direct involvement of mediators activated by dental plaque and involvement of cytokines and heat shock proteins from dental plaque bacteria. There are common predisposing factors which influence both periodontitis and atherosclerosis. Both diseases can be initiated in early childhood, although the first symptoms may not appear until adulthood. The formation of lipid stripes has been reported in 10-year-old children and the increased prevalence of obesity in children and adolescents is a risk factor contributing to lipid stripes development. Endothelium damage caused by the formation of lipid stripes in early childhood may lead to bacteria penetrating into blood circulation after oral cavity procedures for children as well as for patients with aggressive and chronic periodontitis.
Keywords: dospělí; přirozená imunita; zubní plak; Cytokines; dítě; Adult; Chronic Periodontitis; Heat-Shock Proteins; koronární nemoc; cytokiny; lidé; Coronary Disease; Risk Factors; chronická parodontitida; Atherosclerosis; Immunity, Innate; rizikové faktory; Dental Plaque; ateroskleróza; exprese genu; Child; proteiny teplotního šoku; Gene Expression; Humans